STRATEGI PERTUMBUHAN DANA PIHAK KETIGA PADA BANK SINARMAS - Michael Tactria; Slamet Ario Susanto; Ahmad Mukhlis Yusuf (Journal of Applied Finance & Accounting, 2012)
The high level of competition in banking to attain Third Party Funds (TPF), spurs banks to continue to lure customers in a variety of ways, starting with improving operational performance, and improving services, to the diversification of products and use of attractive incentive gifts. Sinarmas business group, which recently took over ownership of one of the foreign exchange banks, also must try to anticipate and formulate appropriate strategies to win over the competition in terms of raising public funds. The purpose of this study was to determine the most appropriate strategy for Bank Sinarmas to conduct third-party funds. Methods of research were carried out by referring to the framework of the strategy, after the comparison, the data obtained from the literature study, and various other sources.